2016
DOI: 10.14336/ad.2015.1026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Leucine-rich Repeat Kinase 2 Variant on Motor and Non-motor Symptoms in Chinese Parkinson’s Disease Patients

Abstract: The G2385R variant of the leucine-rich repeat kinase 2 (LRRK2) is strongly associated with Parkinson’s disease (PD) in Asian populations. However, it is still unclear whether the clinical phenotype of PD patients with the G2385R variant can be distinguished from that of patients with idiopathic PD. In this study, we investigated motor and non-motor symptoms of LRRK2 G2385R variant carriers in a Chinese population. We genotyped 1031 Chinese PD patients for the G2385R variant of the LRRK2 gene, and examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 35 publications
4
28
2
Order By: Relevance
“…However, the progression of the disease after onset might be slightly accelerated in LRRK2 carriers when compared to noncarriers (Oosterveld et al., ). Finally, some studies highlighted the possibility of differences in the prevalence and timing of onset of nonmotor symptoms (REM sleep disorder, cognitive deficits), especially in PD with dementia (Goldwurm et al., ; Sun et al., ). In summary, the striking clinical overlap between LRRK2 mutation carriers with PD and PD without LRRK2 mutations suggests common disease mechanisms.…”
Section: Rationale For a Meaningful Interaction Between Lrrk2 And α‐Smentioning
confidence: 99%
“…However, the progression of the disease after onset might be slightly accelerated in LRRK2 carriers when compared to noncarriers (Oosterveld et al., ). Finally, some studies highlighted the possibility of differences in the prevalence and timing of onset of nonmotor symptoms (REM sleep disorder, cognitive deficits), especially in PD with dementia (Goldwurm et al., ; Sun et al., ). In summary, the striking clinical overlap between LRRK2 mutation carriers with PD and PD without LRRK2 mutations suggests common disease mechanisms.…”
Section: Rationale For a Meaningful Interaction Between Lrrk2 And α‐Smentioning
confidence: 99%
“…Of note, we did not include the original WOQ-19 description [ 4 ] because it was an adaptation of WOQ-32, as was WOQ-9 [ 5 ]. In addition to these articles, we exclude 17 more because they did not use the target questionnaires; among these 17, two more were from the same 32-item questionnaire [ 3 , 21 ] and 15 from other means of assessment [ 22 36 ]. One article was not used because it lacked any type of language validation [ 37 ], and two articles presented post hoc analyses of the same populations outlined in other articles that we include [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we found the LRRK2 G2385R variant could be a risk factor for the PIGD phenotype, motor uctuations, LED values and RBD symptoms in PD patients. But the features of LRRK2 S1647T variant and the LRRK2 haplotypes was not explored in the previous study [7]. Thus, in this study, we aimed to explore the clinical features of PD patients with the LRRK2 S1647T variant and the LRRK2 haplotypes.…”
Section: Backgroundsmentioning
confidence: 96%